Desarrollo de software educativo Q-BOX para mejorar el aprendizaje estratégico de biología en los estudiantes del 4to grado de secundaria de la I.E Manuel Segundo del Águila - Rimay Coral, Paco (2012)
The research has been aimed at developing educational software Q-Box as interactive teaching tool to improve strategic learning biology students in the fourth grade of secondary education in the !E "Manuel Segundo Velasquez Eagle" - Rioja. The hypothesis was formulated on the assumption that the application of QBox Educational software, significantly improve strategic learning of Biology in the fourth grade students of secondary education in the lE "Manuel Segundo Veiasquez Eagien - Rioja. The variabies are organized into two independent variable, represented by Education Software Q-Box and dependent variable, regards strategic learning in biology. The study was conducted with 44 students corresponding to the study sample, determined by non-probability sampling, section "B" corresponds to the experimental group and the "C" was the control group. The type was applied research, experimentallevel, design of pretest- posttest control group, located in quasi-experimental designs. Students were administered a test to evaluate strategic learning in biology, before and after application of educational software "Q- BOX". After analyzing the results it is concluded that the application of Q-Box Educational software has significantly improved strategic learning of Biology in the · fourth grade students of secondary education in the lE "Manuel Segundo Velasquez Eagle" - Rioja, with calculated z (6,53) greater than the tabulated z value (1 ,64). The experimental group, the level of strategic learning in biology qualified as baseline (100%) in the pre-test, post test, the highest percentage (82,61%) got score that is at expected accomplishment. The control group, the level of strategic learning in biology qualified as baseline (100%) in the pre-test, post test, the highest percentage (82,61%) got score that lies in the process.